Cluster randomised controlled trial evaluation of a Link Worker–delivered intervention to improve uptake of diabetic retinopathy screening in a South Asian population. (July 2014) - Bush, Kate; Thomas, Ruth; Raymond, Neil T; Sankar, Sailesh; Barker, Peter J; O'Hare, J Paul
Attendance at diabetic retinopathy screening in minority ethnic groups, including the South Asian population, is known to be poor. We describe a cluster randomised controlled trial conducted in 10 general practitioner (GP) surgeries in Coventry, UK, during 2007 which aimed to evaluate the use of a Link Worker–delivered intervention to improve attendance. The intervention consisted of a simple telephone reminder with the main outcome measure being attendance at diabetic retinopathy screening. We found a statistically significant difference between mean attendance proportions for intervention (0.89) and control (0.74) practices: difference (95% confidence interval (CI)) 0.15 (0.04–0.27), t = 3.03, p = 0.0162; this difference remained significant when adjusted for previous year's proportions. In this proof-of-concept study, in inner city Coventry, we demonstrated increased attendance at diabetic retinopathy screening by use of a simple Link Worker–implemented telephone call intervention. The use of Link Worker phone calls may be a useful tool to increase attendance for diabetic retinopathy screening in a group with high did-not-attend (DNA) rates and a high prevalence of diabetic retinopathy and visual impairment.